EMPLOYING OF COOPERATIVE LEARNING MODEL MAKE A MATCH TYPE AIDED SPEAKING CARD MEDIA AS AN EFFORT TO IMPROVE THE LEARNING OUTCOMES OF STUDENTS - Keke Citra Wahyu A (Satya Widya, 2017)
The purpose of this research is to improve mathematic learning outcomes of students  grade 3 of State Elementary School Kupang 03 district Ambarawa by using cooperative learning model of Make A Match type assisted by Speaking Card media. This study used a classroom action research that consists of two cycles. At each cycle consists of four stages: planning, action, observation, and reflection. The instrument data collection using interviews, observations, and mathematics courses test questions about the material flat wake. Data analysis was performed by using a comparative descriptive analysis that compares the initial conditions before the procedure, the results of the first cycle and the second cycle. The results showed that the cooperative learning model of Make A Match type assisted Speaking Card media can improve learning outcomes learners are seen from the test results. The increase in the average grade of 69.7 pre-cycle, the first cycle of 75.5 and 81.6 second cycle. The increase also occurred in the percentage of the number of learners who achieve a minimum completeness criteria (KKM). In the pre-cycle percentage achievement of KKM 62.8% (22 students), in the first cycle percentage increased to 82.8% (29 students), and the second cycle built up became percentage increase of 100% (35 students).